AB0157 Serum Level of the Vascular Endothelial Growth Factor is Elevated in Ankylosing Spondylitis and Osteocalcin May be Related Wth Osteoproliferation. (9th June 2015) - Solmaz, D.; Bulbul, H.; Uslu, S.; Kozaci, L.D.; Karaca, N.; Akar, S.
Abstract : Background: Ankylosing spondylitis (AS) is a chronic rheumatic disease characterized by sacroiliac and spinal inflammation and new bone formation (syndesmophyte). Molecular mechanisms underlying this process have not been yet fully understood however differentiation of mesenchymal cells into bone-forming osteoblasts appears to be a key pathogenic event. Vascular endothelial growth factor (VEGF) is a potent angiogenic factor and have some pro-inflammatory activity. It has also been suggested that VEGF may be relevant for new bone formation in AS. Objectives: To evaluate the serum VEGF and osteocalcin levels in patients with AS. We also assessed the relationship among VEGF/osteocalcin levels and disease related parameters including radiographic outcomes. Methods: In total 98 consecutive AS patients (77 males [79%]; with a mean age of 39.3±10.0 years) according to the modified New York criteria and 49 healthy controls (37males [76%]; with a mean age of 39.0±5.9 years) from two centers were included in the study. Serum VEGF, osteocalcin, interleukin (IL)-8, IL-6 levels were measured by commercially available ELISA kits. We also determined the serum high-sensitivity C-reactive protein (hs-CRP) levels. Disease related characteristics of patients were assessed by using BASDAI, BASFI, BASMI. Radiographs of the pelvis, cervical and lumbar spine were scored by using the modified New York and modified Stokes ankylosing spondylitis spinal score (mSASSS). Results: Age and sex distribution were not different between AS patients and control subjects. As expected hs-CRP levels and erythrocyte sedimentation rate were higher in AS patients in comparison with controls. Serum VEGF level was found to be significantly higher in our AS patients compared with controls. In our study group serum VEGF levels were correlated with hs-CRP (rho=0.285 and P =0.005), ESR (rho=0.247 and P =0.015), IL-6 level (rho=0.380 and P <0.001), IL-8 (rho=0.400 and P <0.001) and ASDAS-CRP (rho=0.203 and P =0.048). Serum VEGF level was found to be not associated with hip involvement, sacroiliac joint ankylosis or presence of the syndesmophyte. Our study showed that although serum osteocalcin level was not statistically different in AS patients and controls it was significantly higher in patients with sacroiliac joint ankylosis and hip involvement. Conclusions: The results of the present study showed that VEGF may be a good indicator of disease activity in AS and osteocalcin may have a role in new bone formation. Disclosure of Interest: None declared